Revision of world species of the genus Heptascelio Kieffer (Hymenoptera: Platygastroidea, Platygastridae) - Johnson, Norman F.; Masner, Lubomír; Musetti, Luciana; Noort, Simon Van; K., Rajmohana; Darling, D. Christopher; Guidotti, Antonia; Polaszek, Andrew (Zootaxa, 2008)
The world species of the genus Heptascelio Kieffer (Hymenoptera: Platygastroidea, Platygastridae) are revised. The generic concept is expanded and the genus is redescribed. Eighteen species are recognized, of which only two were described previously: H. lugens Kieffer (Philippines) and H. striatosternus Narendran & Ramesh Babu (India, Sri Lanka, Nepal, Madagascar). Both species are redescribed, and H. punctisternus Narendran & Ramesh Babu is considered a junior synonym of H. striatosternus (new synonymy). The following species are described as new: H. albipes Masner, van Noort & Johnson, n.sp. (Cameroon, Gabon, Uganda); H. anthonyi Masner & Johnson, n.sp. (Zimbabwe); H. aquilinus Masner & Johnson, n.sp. (South Africa); H. bivius Johnson & Masner, n.sp. (Indonesia); H. castor Masner & Johnson, n.sp. (Indonesia, Malaysia); H. dayi Masner & Johnson, n.sp. (Indonesia); H. dispar Masner & Johnson, n.sp. (Botswana, Namibia, South Africa); H. hamatus Masner & Johnson, n.sp. (Thailand, Laos, Vietnam, Malaysia, Indonesia, Taiwan); H. lateralis Johnson, van Noort & Masner (Central African Republic, Gabon); H. noyesi Masner & Johnson, n.sp. (Madagascar); H. orarius Johnson & Masner, n.sp. (Madagascar); H. paralugens Masner & Johnson, n.sp. (Philippines); H. sicarius Johnson & Musetti, n.sp. (Madagascar), H. strigatus Masner, Johnson & van Noort, n.sp. (Gabon, Central African Republic); H. teres Johnson & Masner, n.sp. (Madagascar), and H. watshami Masner & Johnson, n.sp. (Democratic Republic of Congo, Kenya, Malawi, Zimbabwe). Heptascelio watshami has been reared from the eggs of Plagiotriptus pinivorus Descamps (Orthoptera: Thericleidae), a pest of pine. An electronic version of the identification key is available at WaspWeb at http://www.waspweb.org/ Platygastroidea/Keys/. The electronic version of this document has been formatted with embedded links to additional resources available online via the internet both to enhance the content and as a demonstration of the utility of international standards for biodiversity informatics.